2020
DOI: 10.1159/000505536
|View full text |Cite
|
Sign up to set email alerts
|

Platelet Dysfunction and Its Role in the Pathogenesis of Psoriasis

Abstract: Background: Psoriasis is an immune-mediated inflammatory skin disease in conjunction with the systemic inflammatory process. It appears to be related to increased risks of cardiovascular disease events, especially in severe cases. The hemostatic balance is disrupted due to the prothrombotic bias in psoriasis, which might be mainly preserved by platelet hyperactivity. Platelets are also immune cells that initiate and regulate immune and inflammatory processes, except as the principal mediator of hemostasis and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
23
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 95 publications
0
23
1
Order By: Relevance
“…PLR, along with its potential to predict disease severity, was investigated in several neoplastic, prothrombotic, and metabolic diseases. Its role has been attributed to increased thrombogenic activity (24)(25)(26). These results demonstrated that PLR could be used as an indicator of disease severity in AS patients.…”
Section: Discussionmentioning
confidence: 83%
“…PLR, along with its potential to predict disease severity, was investigated in several neoplastic, prothrombotic, and metabolic diseases. Its role has been attributed to increased thrombogenic activity (24)(25)(26). These results demonstrated that PLR could be used as an indicator of disease severity in AS patients.…”
Section: Discussionmentioning
confidence: 83%
“…In recent years, it has been increasingly recognized that platelet activation seems to be a major pathogenic factor in psoriasis (Elbers et al, 2010), and platelet activation indexes generally suggest abnormal platelet function and are given an additional role in the diagnosis of psoriasis. Platelets are also immune cells that initiate and regulate immune and inflammatory processes, except as the principal mediator of hemostasis and thrombosis, and platelet dysfunction is deeply involved in the pathogenesis of psoriasis (Fan et al, 2020).The platelet activating factor has been reported in coronary heart disease with blood-stasis syndrome (Zheng et al, 2012) and primary dysmenorrhea with blood-stasis tongue figure (Yang and Chen, 2011), but there is no report in psoriasis with blood-stasis. PAF cannot be a characteristic diagnostic marker of psoriasis disease, but it is expected to be used as potential biomarkers for diagnosis and differentiation of blood-stasis syndrome in PV, and the increase of platelet-activating factor may be a pathogenesis of blood-stasis syndrome.…”
mentioning
confidence: 99%
“… 38 A possible explanation lies in that platelets are the major source of the cytokines such as IL-1β, and increased activation of them is believed to be involved in the development and progression of inflammation. 39 …”
Section: Discussionmentioning
confidence: 99%
“…38 A possible explanation lies in that platelets are the major source of the cytokines such as IL-1β, and increased activation of them is believed to be involved in the development and progression of inflammation. 39 In addition to F2RL3, GP9 and ITGA2B genes were found to be involved in platelet activation. ITGA2B encodes integrin alpha-IIb/beta-3, which is a receptor for fibronectin, fibrinogen, plasminogen, prothrombin, thrombospondin.…”
Section: Discussionmentioning
confidence: 99%